Reimagining Classroom Equality: An Academic Inquiry into Surah Al-Fatihah’s Core Values for Inclusivity in Education - Taufikin, Taufikin; Nurhayati, Sri; Harun, Makmur (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
This study examines the potential of Surah Al-Fatihah, often regarded as the spiritual bedrock of the Qur’an, to serve as a framework for fostering inclusive educational environments. By aligning its core values—compassion, equity, and guidance—with contemporary educational discussions on empathy and resilience, this investigation demonstrates how faith-based principles can enrich diverse instructional settings while adhering to secular educational standards. Using an interpretative methodology and a thematic review of educational literature, the study explores the application of Surah Al-Fatihah's values in practical teaching strategies, such as the incorporation of empathy-driven classroom practices, collaborative learning models, and personalized support for students' emotional well-being. Integrating perspectives from Islamic pedagogy, culturally responsive teaching, and inclusive pedagogical models, the research shows how these principles can influence classroom management, curriculum design, and teacher-student interactions. Through textual analysis and observations in real-world educational settings, the findings underscore how embedding these values enhances student engagement, promotes emotional welfare, and boosts academic performance. Educators who intentionally integrate compassion, equity, and guidance into their teaching approaches report reduced stress levels, increased collaboration, and greater cultural sensitivity. The study’s discussion addresses how these outcomes can help overcome systemic challenges—such as limited institutional support and sociocultural biases—by focusing on moral imperatives in teaching practices. Ultimately, Surah Al-Fatihah emerges as a powerful moral and spiritual framework for inclusive education, strengthening culturally responsive strategies and fostering both academic success and social cohesion. The implications suggest the need for continuous professional development, cross-cultural validation, and policy interventions to fully integrate these Quranic values into educational systems.